Analysis of the Implementation of Picture Card Media to Improve Basketball Skills in Elementary School Children - I Putu Agus Dharma Hita; Mayasari; Sri Hardianty; Gamar Al Haddar; Salfin; Jasiah (Jurnal Ilmiah Multidisipin, 2023)
Background. This research explores the implementation of picture card media to enhance basketball-playing skills among primary school children Purpose. Grounded in a literature review, the study addresses the challenges in fostering interest and understanding of basketball concepts at the elementary level. Method. Utilizing a comprehensive literature review methodology, key theories of early childhood learning, and the efficacy of visual aids are examined. Results. The analysis indicates that the integration of picture card media has the potential to overcome challenges related to children's comprehension of the game, enhancing both cognitive and motor skills. However, potential obstacles such as limited teacher training and resource availability must be carefully considered for successful implementation. Conclusion. The study concludes by highlighting the need for a holistic and culturally sensitive approach in designing educational strategies, ensuring the media's visual content aligns with the children's cultural context. The findings of this literature review provide a theoretical foundation for future empirical research, emphasizing the significance of tailored approaches to support effective learning experiences for primary school children in basketball.